2018
DOI: 10.5194/bg-15-1795-2018
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and forest structure explain the temperature sensitivity patterns of productivity in temperate forests

Abstract: Abstract. Rising temperatures due to climate change influence the wood production of forests. Observations show that some temperate forests increase their productivity, whereas others reduce their productivity. This study focuses on how species composition and forest structure properties influence the temperature sensitivity of aboveground wood production (AWP). It further investigates which forests will increase their productivity the most with rising temperatures. We described forest structure by leaf area i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…However, stand-scale models, such as individual-based gap models, have also been used to explore forest dynamics under climate-change scenarios (Bugmann & Fischlin, 1996;Collalti et al, 2018;Fischer et al, 2014;Pastor & Post, 1986;Reyer, 2015;Shugart et al, 2018). Such finer-scale models can further inform the role of forest composition and structure in shaping forest responses to environmental drivers (Bohn et al, 2018;Fyllas et al, 2017). Additionally, SDMs have been used…”
Section: Forest Responses To Global Changementioning
confidence: 99%
“…However, stand-scale models, such as individual-based gap models, have also been used to explore forest dynamics under climate-change scenarios (Bugmann & Fischlin, 1996;Collalti et al, 2018;Fischer et al, 2014;Pastor & Post, 1986;Reyer, 2015;Shugart et al, 2018). Such finer-scale models can further inform the role of forest composition and structure in shaping forest responses to environmental drivers (Bohn et al, 2018;Fyllas et al, 2017). Additionally, SDMs have been used…”
Section: Forest Responses To Global Changementioning
confidence: 99%
“…Sustainably maintaining multifunctional forest ecosystems has become a widespread objective of forest management (Manning et al 2018;Schmithüsen 2008). This development increases the interest in analyzing the potentially strong influence of tree species diversity (Paquette and Messier 2011;Gamfeldt et al 2013;Liang et al 2016) and forest structure on ecosystem functions and services (Felipe-Lucia et al 2018;Bohn et al 2018;Bohn and Huth 2017). Previously established monospecific and even-aged forests had the aim of a high yield and the homogeneous provision of a narrow range of predominant products, which were produced with the aim to provide a homogeneous product quality (Puettmann et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the connection between forest structure and plant diversity, which we also wanted to test, and how it is linked to variables such as diameter size distribution, heights, basal area, wood stock, vegetation cover in different layers of the forest (vertical structure [24]), or tree density and age [25][26][27], all of which are modifiable by management [28]. Management directed at changing stand structure variables can significantly affect plant diversity in the understory by altering environmental factors such as light and water availability [29][30][31][32][33][34]. Nevertheless, factors other than forest structure, such as soil characteristics or stage of development (crop age [24]) can influence plant community composition and diversity.…”
Section: Introductionmentioning
confidence: 99%